PRODUK FERMENTASI DAN PRODUKSI GAS SECARA INVITRO DARI RANSUM YANG MENGANDUNG DAUN KELOR (MORINGA OLEIFERA, LAMM) - Marhaeniyanto, Eko; Susanti, Sri (BUANA SAINS, 2014)
This research was designed to find out the best composition between Moringa oleifera and other concentrate material as a supplier of protein by-pass and contain of secondary compounds tannin. Four kinds of concentrate consisted of various levels of Moringa oleifera leaf, Samanea saman leaf, Coconut cake and Onggok. These concentrate would combined with three of feeding forages proportion namely straw Zea mays. The feed digestibility in vitro and gas production in incubation of 48 hours showed that there were highly significant differences (P 0.01) between each treatment, which highest value was the addition without Moringa oleifera leaf and Samanea saman leaf. The enhanced levels of Moringa oleifera leaf is lower digestibility. Levels of N-NH3 rumen fluid for 4, 12 and 24 hours decreased with the increasing levels of use of Moringa oleifera leaf. There were positive response on feeding supplements based Moringa oleifera leaf due to supply sufficient nutrients for rumen microbes. Based on crude protein 36.55% content of Moringa oleifera could be developed as feed supplement. It could be conclude that the utilization of concentrate feed (Moringa oleifera leaf of 30% : Samanea saman leaf of 10%: coconut cake of 45%: onggok of 15%) with the proportion of 50% forage : concentrate of 50%, potentially as a alternative supplements source for ruminants in Indonesia